Changes in the number of chick ciliary ganglion neuron processes with time in cell culture (The Rockefeller University Press, 1987)
The purpose of this study was to describe the shape of chick ciliary ganglion neurons dissociated from embryonic day 8 or 9 ganglia and maintained in vitro. Most of the neurons were multipolar during the first three days after plating, with an average of 6.0 processes extending directly from the cell body. The neurons became unipolar with time. The remaining primary process accounted for greater than 90% of the total neuritic arbor. This striking change in morphology was not due to the selective loss of multipolar cells, or to an obvious decline in the health of apparently intact cells. The retraction of processes was neither prevented nor promoted by the presence of embryonic muscle cells. Process pruning occurred to the same extent and over the same time course whether the cells were plated on a monolayer of embryonic myotubes or on a layer of lysed fibroblasts. Process retraction is not an inevitable consequence of our culture conditions. Motoneurons dissociated from embryonic spinal cords remained multipolar over the same period of time. We conclude that ciliary ganglion neurons breed true in dissociated cell culture in that the multipolar-unipolar transition reflects their normal, in vivo, developmental program.